Evaluation of the Merdeka Curriculum using the Kirkpatrick Model in Secondary Education: An Empirical Study - Putri Rahmadani Nasution; Muhammad Bukhori Dalimunthe (Universitas Pendidikan Ganesha, 2026)
This study aims to evaluate the Merdeka Curriculum in economics subjects using the Kirkpatrick model at SMA Negeri 2 Percut Sei Tuan. This study uses primary data where data is collected using a questionnaire and uses secondary data where data and information are needed by reading books, data from the internet, theses, or dissertations and previous research. This study was conducted on teachers and students at SMA Negeri 2 Percut Sei Tuan, where 3 teachers and 235 students were the samples in this study. The results of the analysis show that the evaluation of the reaction, learning, behavior, and result stages contributed to the merdeka curriculum in economics subjects at SMA Negeri 2 Percut Sei Tuan. Where, the evaluation of the learning stage has the highest contribution among the other evaluation stages to the merdeka curriculum program. Meanwhile, the evaluation of the behavior stage has the lowest contribution among the other evaluation stages to the Merdeka Curriculum program. This research provides insights from a program evaluation perspective, demonstrating that the Merdeka Curriculum contributes to improving the quality of classroom learning. It also recommends that the behavioral aspect requires additional attention from teachers and school leaders. The research implications contribute to improving the quality of learning and policy development by school leaders through the Merdeka Curriculum.